Peningkatan Kompetensi Melalui Edukasi Aplikasi Coretax Administration System (CTAS) pada Bendaharawan di Kota Depok - Sixpria, Nedsal; Fatimah, Hayati; Ramadhani, Annisa Alifa; Sahputri, Meisy Hartivia; Revikasha, Dimas Fayed; Safitri, Hafizhah (Keris: Journal of Community Engagement, 2025)
The problem faced by partners is that not all treasurers can access or manage Coretax independently without technical assistance, thus hampering the daily tax process. Coretax education training held for the treasurers of Khidmat Sehat Afiat (Kisa) Regional General Hospital, Depok City, Anugerah Sehat Afiat Regional General Hospital, Beji District and Beji District Community Health Center aims to improve understanding and technical skills in using the digital-based tax administration system, Coretax, developed by the Directorate General of Taxes. The scope of the training includes the process of taxpayer registration, recording withholding tax evidence, reporting Tax Returns (SPT), creating tax billing codes, as well as integrated tax data management through the Coretax application. The training method is conducted through technical guidance  with a hands-on approach on the Coretax system, involving simulations and case studies in accordance with the treasurer’s business processes in health service units. The training results showed an increase in the treasurers’ ability to operate the Coretax application independently, understand tax obligations, and optimize more effective and accurate tax reporting and administration. In conclusion, this training successfully strengthened the technical capacity of the treasurers Khidmat Sehat Afiat (Kisa) Regional General Hospital, Depok City, Anugerah Sehat Afiat Regional General Hospital, Beji District and Beji District Community Health Center in supporting the digital transformation of tax administration, which ultimately supports increased tax compliance and transparent financial governance in the public health sector.